Expression of SofLAC, a new laccase in sugarcane, restores lignin content but not S:G ratio of Arabidopsis lac17 mutant - Cesarino, Igor (Journal of experimental botany, 2013)
Lignin is a complex phenolic heteropolymer deposited in the secondarily thickened walls of specialized plant cells to provide strength for plants to stand upright and hydrophobicity to conducting cells for long-distance water transport. Although essential for plant growth and development, lignin is the major plant cell-wall component responsible for biomass recalcitrance to industrial processing. Peroxidases and laccases are generally thought to be responsible for lignin polymerization, but, given their broad substrate specificities and large gene families, specific isoforms involved in lignification are difficult to identify. This study used a combination of co-expression analysis, tissue/cell-type-specific expression analysis, and genetic complementation to correlate a sugarcane laccase gene, SofLAC, to the lignification process. A co-expression network constructed from 37 cDNA libraries showed that SofLAC was coordinately expressed with several phenylpropanoid biosynthesis genes. Tissue-specific expression analysis by quantitative RT-PCR showed that SofLAC was expressed preferentially in young internodes and that expression levels decrease with stem maturity. Cell-type-specific expression analysis by in situ hybridization demonstrated the localization of SofLAC mRNA in lignifying cell types, mainly in inner and outer portions of sclerenchymatic bundle sheaths. To investigate whether SofLAC is able to oxidize monolignols during lignification, the Arabidopsis lac17 mutant, which has reduced lignin levels, was complemented by expressing SofLAC under the control of the Arabidopsis AtLAC17 promoter. The expression of SofLAC restored the lignin content but not the lignin composition in complemented lac17 mutant lines. Taken together, these results suggest that SofLAC participates in lignification in sugarcane